ChemInform Abstract: Highly Active and Robust Metalloporphyrin Catalysts for the Synthesis of Cyclic Carbonates from a Broad Range of Epoxides and Carbon Dioxide. Issue 39 (8th September 2016) - Maeda, Chihiro; Shimonishi, Junta; Miyazaki, Ray; Hasegawa, Jun‐ya; Ema, Tadashi
Abstract: The title reaction is successfully applied to mono‐ and 1, 1‐ as well as 1, 2‐disubstituted terminal and internal epoxides as well as diepoxides.